2012
DOI: 10.1590/s0066-782x2012005000020
|View full text |Cite
|
Sign up to set email alerts
|

Estudo transversal das estratégias de tratamento clínico na fibrilação atrial

Abstract: Background: Despite the high prevalence and clinical importance of atrial fibrillation (AF), there is no Brazilian study describing the clinical profile of patients with AF and the most used treatment strategy (rhythm control vs. rate control).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Num estudo realizado por OLIVEIRA et al, 2012, no Brasil, observou-se uma relação estatisticamente significativa entre a pressão arterial elevada e a ingestão de carne, contrariamente ao que foi possível observar nos resultados encontrados (Oliveira et al, 2012).…”
Section: Lipoproteína De Baixa Densidadeunclassified
“…Num estudo realizado por OLIVEIRA et al, 2012, no Brasil, observou-se uma relação estatisticamente significativa entre a pressão arterial elevada e a ingestão de carne, contrariamente ao que foi possível observar nos resultados encontrados (Oliveira et al, 2012).…”
Section: Lipoproteína De Baixa Densidadeunclassified
“…O TTR da anticoagulação para FA variou de 31% a 67% nos estudos. 210 , 233 , 235 - 238 No registro prospectivo RECALL de pacientes com FA, o TTR médio (desvio-padrão) para o período do estudo foi 49,5% (27,5). Durante o seguimento, o uso de anticoagulantes e o INR na faixa terapêutica aumentaram para 87,1% e 59,1%, respectivamente.…”
Section: Utilização E Custo Da Atenção à Saúdeunclassified
“…The TTR of anticoagulation for AF has ranged from 31% to 67% in the studies. 210 , 233 , 235 - 238 In the RECALL prospective registry of AF patients, mean (standard deviation) TTR for the study period was 49.5% (27.5). During follow-up, the use of anticoagulants and INR in the therapeutic range increased to 87.1% and 59.1%, respectively.…”
Section: (Refer To Tables 1-1 Through 1-7 and Charts 1-1 And 1-7)mentioning
confidence: 99%
“…Beta-blockers were prescribed for 81% of the patients in rate control. 280 Amiodarone was mentioned by 83% of the doctors as the choice for rhythm control strategy. 281 • Data from 125 primary care centers have found that, among the patients with AF (n=301), 91 (30.2%) were not receiving any type of treatment for rate or rhythm control.…”
Section: Awareness Treatment and Control Anticoagulationmentioning
confidence: 99%